2018
DOI: 10.1038/s41433-018-0043-1
|View full text |Cite
|
Sign up to set email alerts
|

Higher retinal vessel oxygen saturation: investigating its relationship with macular oedema in retinitis pigmentosa patients

Abstract: Based on our results, the presence of macular oedema indicates a tendency toward greater alteration of the metabolic function in RP patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 44 publications
2
22
0
Order By: Relevance
“…These findings were more pronounced in patients with rod-cone dystrophy (RCD) [ 38 , 39 , 40 ]. Furthermore, the oxygen saturation values correlated well with structural and functional changes [ 39 , 41 , 42 , 43 ]. In addition, peripapillary retinal vessel diameters were reduced proportionally to the functional and structural changes [ 39 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings were more pronounced in patients with rod-cone dystrophy (RCD) [ 38 , 39 , 40 ]. Furthermore, the oxygen saturation values correlated well with structural and functional changes [ 39 , 41 , 42 , 43 ]. In addition, peripapillary retinal vessel diameters were reduced proportionally to the functional and structural changes [ 39 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the amount of peripapillary RNFL structural changes correlates well with the metabolic alterations detected by RO in IRDs [ 39 ]. In addition, the presence of cystoid macular edema (CME) in OCT imaging, reported to occur in 10%–50% of retinitis pigmentosa patients [ 51 , 52 , 53 , 54 ], has been well associated with the best-corrected visual acuity [ 55 , 56 ] and also with the degree of metabolic alterations and foveal vascular anomalies in RCD [ 42 , 57 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on the application of RO in patients with IRDs showed the oxygenation in retinal vessels of the inner retina to be affected (Eysteinsson et al 2014; Todorova et al 2014; Türksever et al 2014; Battu et al 2015; Ueda‐Consolvo et al 2015; Todorova et al 2016; Zong et al 2016; Bojinova et al 2017; Todorova 2017; Bojinova et al 2018; Waizel et al 2018a), thus confirming an altered metabolic function as a result of a degenerative process of the outer retina. For rod–cone dystrophies, strong correlations have been found between the retinal metabolic demand and the structural (Türksever et al 2014; Bojinova et al 2017; Bojinova et al 2018) and functional alterations (Todorova et al 2016; Bojinova et al 2018). Even if not applicable in children, transcorneal electrical stimulation is currently the only evidence‐based therapeutic modality in elderly RCD patients with visual acuity over light perception, where RO has already confirmed its value to serve as an objective and sensitive monitoring method (Della Volpe‐Waizel et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that changes of the retinal vasculature with vessel attenuation are a hallmark of RP [4][5][6][7][8][9][10][11]. In this context, swept-source coherence tomography angiography (OCTA) that allows for a non-invasive depth-resolved visualisation of the retinal and choroidal microvasculature in vivo might be useful as a monitoring method for TES treatment.…”
Section: Introductionmentioning
confidence: 99%